MENJADI GURU PROFESIONAL DI ERA DIGITAL: PEMANFAATAN MEDIA PEMBELAJARAN DIGITAL DAN MEDIA SOSIAL - Imaniah, Ikhfi; Al Manar, Muhammad Abduh (Universitas Muhammadiyah Tangerang, 2022)
Social media has become an important part of learning. However, the adoption of E-learning and technology in learning resulted in a new teaching era among all educators all over the world. As the COVID-19 hit the world of education, education shifted the learning from face to face learning into distance learning. The following study discussed the implementation of technology in the new era of education during community service programs. Qualitative research was implemented through a week intensive observation by the researchers focusing on media of learning creation, use of digital media in learning and gamification of learning. Based on the data from the study, 48% of the participants had difficulty accessing technology in learning. The researchers also suggested that social media have a significant role to create fun and interactive learning. Moreover, applications such as Canva, Powtoon, Prezi and Kinemaster can be a great tool and media in a new and modern era of learning.